Managing Multiple Mobile Resources - Feldkord, Björn; Knollmann, Till; Malatyali, Manuel; Meyer auf der Heide, Friedhelm (Theory of Computing Systems)

Divide and Conquer: Hierarchical Network and Service Coordination - Schneider, Stefan Balthasar; Jürgens, Mirko; Karl, Holger (IFIP/IEEE International Symposium on Integrated Network Management (IM))
In practical, large-scale networks, services are requested by users across the globe, e.g., for video streaming. Services consist of multiple interconnected components such as microservices in a service mesh. Coordinating these services requires scaling them according to continuously changing user demand, deploying instances at the edge close to their users, and routing traffic efficiently between users and connected instances. Network and service coordination is commonly addressed through centralized approaches, where a single coordinator knows everything and coordinates the entire network globally. While such centralized approaches can reach global optima, they do not scale to large, realistic networks. In contrast, distributed approaches scale well, but sacrifice solution quality due to their limited scope of knowledge and coordination decisions. To this end, we propose a hierarchical coordination approach that combines the good solution quality of centralized approaches with the scalability of distributed approaches. In doing so, we divide the network into multiple hierarchical domains and optimize coordination in a top-down manner. We compare our hierarchical with a centralized approach in an extensive evaluation on a real-world network topology. Our results indicate that hierarchical coordination can find close-to-optimal solutions in a fraction of the runtime of centralized approaches.
Keywords: network management; service management; coordination; hierarchical; scalability; nfv

A Nearly Optimal Deterministic Online Algorithm for Non-Metric Facility Location - Bienkowski, Marcin; Feldkord, Björn; Schmidt, Pawel (Proceedings of the 38th Symposium on Theoretical Aspects of Computer Science (STACS))

Development of a hybrid crash-relevant car body component with load-adapted thickness properties: Design, manufacturing and testing - Camberg, Alan Adam; Tröster, Thomas; Latuske, Clemens

A new numerical method for potential anaylsis and design of hybrid components from full vehicle simulations: Implementation and component design - Camberg, Alan Adam; Tröster, Thomas; Wingenbach, Nils; Hielscher, Christian; Grenz, Julian

Generating Physically Sound Training Data for Image Recognition of Additively Manufactured Parts - Nickchen, Tobias; Heindorf, Stefan; Engels, Gregor (Proceedings of the IEEE/CVF Winter Conference on Applications of Computer Vision)

Optical in-situ temperature management for high-quality ZnO molecular beam epitaxy - Albert, M.; Golla, C.; Meier, Cedrik (Journal of Crystal Growth)

Experimental study of two cascaded organic Rankine cycles with varying working fluids - Abbas, Wameedh Khider Abbas; Linnemann, Matthias; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management)

Situation-specific Development of Business Models for Services in Software Ecosystems - Gottschalk, Sebastian (Advanced Software Engineering. Doctorial Consortium)

Bias Silhouette Analysis: Towards Assessing the Quality of Bias Metrics for Word Embedding Models - Spliethöver, Maximilian; Wachsmuth, Henning (Proceedings of the Thirtieth International Joint Conference on Artificial Intelligence, IJCAI-21)
Word embedding models reflect bias towards genders, ethnicities, and other social groups present in the underlying training data. Metrics such as ECT, RNSB, and WEAT quantify bias in these models based on predefined word lists representing social groups and bias-conveying concepts. How suitable these lists actually are to reveal bias - let alone the bias metrics in general - remains unclear, though. In this paper, we study how to assess the quality of bias metrics for word embedding models. In particular, we present a generic method, Bias Silhouette Analysis (BSA), that quantifies the accuracy and robustness of such a metric and of the word lists used. Given a biased and an unbiased reference embedding model, BSA applies the metric systematically for several subsets of the lists to the models. The variance and rate of convergence of the bias values of each model then entail the robustness of the word lists, whereas the distance between the models' values gives indications of the general accuracy of the metric with the word lists. We demonstrate the behavior of BSA on two standard embedding models for the three mentioned metrics with several word lists from existing research.

Generating Informative Conclusions for Argumentative Texts - Syed, Shahbaz; Al-Khatib, Khalid; Alshomary, Milad; Wachsmuth, Henning; Potthast, Martin (Proceedings of the Joint Conference of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Conference on Natural Language Processing (ACL-IJCNLP 2021): Findings)

Syntopical Graphs for Computational Argumentation Tasks - Barrow, Joe; Jain, Rajiv; Lipka, Nedim; Dernoncourt, Franck; Morariu, Vlad; Manjunatha, Varun; Oard, Douglas; Resnik, Philip; Wachsmuth, Henning (Proceedings of the Joint Conference of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Conference on Natural Language Processing (ACL-IJCNLP 2021))

Employing Argumentation Knowledge Graphs for Neural Argument Generation - Al-Khatib, Khalid; Trautner, Lukas; Wachsmuth, Henning; Hou, Yufang; Stein, Benno (Proceedings of the Joint Conference of the 59th Annual Meeting of the Association for Computational Linguistics and the 11th International Joint Conference on Natural Language Processing (ACL-IJCNLP 2021))

Who participated in the GameStop frenzy? Evidence from brokerage accounts - Hasso, Tim; Müller, Daniel; Pelster, Matthias; Warkulat, Sonja (Finance Research Letters)
In January 2021, the GameStop stock was the epicenter of the first case of predatory trading initiated by retail investors. We use brokerage accounts to study who participated in this GameStop frenzy and how they performed. We investigate the extent to which investors’ personal and trading characteristics differ from the general population of retail investors. GameStop traders had a history of investing in speculative instruments, including stocks with lottery-like features. They were also more likely to close their positions before the peak of the bubble. At the onset of the frenzy, numerous retail investors also shorted GameStop. Overall, our results indicate that the GameStop frenzy was not a pure digital protest against Wall Street but speculative trading by a group of retail investors, in line with their prior high-risk trading behavior.
Keywords: Predatory Trading; Retail Investors; Trading Behavior

Tracking control for underactuated non-minimum phase multibody systems - Berger, Thomas; Drücker, Svenja; Lanza, Lukas Johannes; Reis, Timo; Seifried, Robert (Nonlinear Dynamics)
Abstract We consider tracking control for multibody systems which are modeled using holonomic and non-holonomic constraints. Furthermore, the systems may be underactuated and contain kinematic loops and are thus described by a set of differential-algebraic equations that cannot be reformulated as ordinary differential equations in general. We propose a control strategy which combines a feedforward controller based on the servo-constraints approach with a feedback controller based on a recent funnel control design. As an important tool for both approaches, we present a new procedure to derive the internal dynamics of a multibody system. Furthermore, we present a feasible set of coordinates for the internal dynamics avoiding the effort involved with the computation of the Byrnes–Isidori form. The control design is demonstrated by a simulation for a nonlinear non-minimum phase multi-input, multi-output robotic manipulator with kinematic loop.

Inconsistent tax transfer prices: tax filings, audits, and double taxation - Lorenz, Johannes; Sureth-Sloane, Caren; Diller, Markus

Second harmonic generation on excitons in ZnO/(Zn,Mg)O quantum wells with built-in electric fields - Mund, Johannes; Yakovlev, Dmitri R.; Sadofev, Sergey; Meier, Cedrik; Bayer, Manfred (Physical Review B)

Nonlinear Imaging of Nanoscale Topological Corner States - Kruk, Sergey S.; Gao, Wenlong; Choi, Duk-Yong; Zentgraf, Thomas; Zhang, Shuang; Kivshar, Yuri (Nano Letters)
Topological states of light represent counterintuitive optical modes localized at boundaries of finite-size optical structures that originate from the properties of the bulk. Being defined by bulk properties, such boundary states are insensitive to certain types of perturbations, thus naturally enhancing robustness of photonic circuitries. Conventionally, the N-dimensional bulk modes correspond to (N – 1)-dimensional boundary states. The higher-order bulk-boundary correspondence relates N-dimensional bulk to boundary states with dimensionality reduced by more than 1. A special interest lies in miniaturization of such higher-order topological states to the nanoscale. Here, we realize nanoscale topological corner states in metasurfaces with C6-symmetric honeycomb lattices. We directly observe nanoscale topology-empowered edge and corner localizations of light and enhancement of light–matter interactions via a nonlinear imaging technique. Control of light at the nanoscale empowered by topology may facilitate miniaturization and on-chip integration of classical and quantum photonic devices.

Decomposition of Arithmetic Components for the Approximate Circuit Synthesis with EvoApproxLib - Rehnen, Jakob Werner

Forschung und Entwicklung: Kriterien für die Aktivierung in der Unternehmenspraxis - Blankenfeldt, Maximilian; Müller, Jens; Weinrich, Arndt (Intangibles - Immaterielle Werte)

Development of an adaptive, sensor-based FDS-robot-system - Ivanjko, Martin; Beck, Robert; Meschut, Gerson; Zweck, Jonas; Richter, Thomas

EUROGRAPHICS 2021: Education Papers Frontmatter

Untersuchung der Dichtheitseigenschaften hybridgefügter Mischbauverbindungen für den Einsatz in Batteriegehäusen für Elektrofahrzeuge - Schmolke, Tobias; Meschut, Gerson

Reduzierung der Flanschbreiten beim Widerstandspunktschweißen durch Einsatz exzentrischer Elektrodenkappengeometrien - Böhne, Christoph; Tümkaya, Gökhan; Meschut, Gerson (Schweißen und Schneiden)

Practical methods for avoidance of liquid metal embrittlement in resistance spot welds of advanced high strength steels - Böhne, Christoph; Meschut, Gerson; Biegler, Max; Rethmeier, Michael

Application-oriented avoidance of liquid metal embrittlement during resistance spot welding of zinc-coated advanced high strenght steels - Böhne, Christoph; Biegler, Max; Meschut, Gerson; Rethmeier, Michael

Monocular Depth Estimation via Listwise Ranking using the Plackett-Luce Model - Lienen, Julian; Hüllermeier, Eyke; Ewerth, Ralph; Nommensen, Nils (Proceedings of the IEEE/CVF Conference on Computer Vision and Pattern Recognition, CVPR)

Joining of press-hardened profiles for the mixed-intensive lightweight structural design in electric vehicles - Rotzsche, Dirk; Meschut, Gerson; Fuss, Dennis; Bangel, Martin; Uffelmann, Marcel; Werner, Kai; Oleff, Nils; Günter, Heinrich (Joining in Car Body Engineering 2021)

Time-Optimal Construction of Overlays - Götte, Thorsten; Hinnenthal, Kristian; Scheideler, Christian; Werthmann, Julian (Proc. of the 40th ACM Symposium on Principles of Distributed Computing (PODC '21))
We show how to construct an overlay network of constant degree and diameter $O(\log n)$ in time $O(\log n)$ starting from an arbitrary weakly connected graph. We assume a synchronous communication network in which nodes can send messages to nodes they know the identifier of and establish new connections by sending node identifiers. If the initial network's graph is weakly connected and has constant degree, then our algorithm constructs the desired topology with each node sending and receiving only $O(\log n)$ messages in each round in time $O(\log n)$, w.h.p., which beats the currently best $O(\log^{3/2} n)$ time algorithm of [Götte et al., SIROCCO'19]. Since the problem cannot be solved faster than by using pointer jumping for $O(\log n)$ rounds (which would even require each node to communicate $Ω(n)$ bits), our algorithm is asymptotically optimal. We achieve this speedup by using short random walks to repeatedly establish random connections between the nodes that quickly reduce the conductance of the graph using an observation of [Kwok and Lau, APPROX'14]. Additionally, we show how our algorithm can be used to efficiently solve graph problems in hybrid networks [Augustine et al., SODA'20]. Motivated by the idea that nodes possess two different modes of communication, we assume that communication of the initial edges is unrestricted. In contrast, only polylogarithmically many messages can be communicated over edges that have been established throughout an algorithm's execution. For an (undirected) graph $G$ with arbitrary degree, we show how to compute connected components, a spanning tree, and biconnected components in time $O(\log n)$, w.h.p. Furthermore, we show how to compute an MIS in time $O(\log d + \log \log n)$, w.h.p., where $d$ is the initial degree of $G$.

Skill-based worker assignment in a manual assembly line - Gräßler, Iris; Roesmann, Daniel; Cappello, Chiara; Steffen, Eckhard (Procedia CIRP Design)

Spannungsbasierte Lebensdauerberechnung von zyklisch beanspruchten Klebverbindungen mit hyperelastischem Deformationsverhalten - Çavdar, Serkan
Im Rahmen der Mischbau-Modulbauweise gewinnt das Fügen von artverschiedenen Werkstoffen mit hyperelastischen Klebstoffsystemen zunehmend an Bedeutung. Um diese auch unter zyklischer Beanspruchung sicher und effizient auszulegen, wird in der vorliegenden Arbeit eine Methode für die spannungsbasierte Lebensdauerberechnung von 2K-PU-Klebverbindungen unter Berücksichtigung von iso- sowie anisotropen Fügeteilwerkstoffen aufgezeigt. Ausgehend von den theoretischen Grundlagen wird das Deformations- und Versagensverhalten einer repräsentativen 2K-PU-Klebverbindung in Grundversuchen mit steifen Fügeteilen unter quasistatischer und zyklischer Belastung experimentell untersucht. Dies bildet die Basis für die Modellierung des Klebschichtversagens in Abhängigkeit der Beanspruchungsmehrachsigkeit. Anhand von im Detail aufgebauten FE-Modellen der untersuchten Verbindungen werden die notwendigen Ansatzparameter identifiziert, verifiziert und in einer Sensitivitätsanalyse hinsichtlich der Klebschichtdiskretisierung in Bezug auf ihre Robustheit und einfache Anwendbarkeit bewertet. Eine abschließende Validierung der entwickelten Methode erfolgt mit zunehmender Komplexität an technologischen und bauteilähnlichen Verbindungsproben. Die Gegenüberstellung der numerisch berechneten mit der experimentellen Anriss- und Versagenslebensdauer belegt ein hohes Maß an Sicherheit und trägt somit zum Vertrauen in die Fügetechnologie Kleben bei.
Keywords: Lebensdauerberechnung; numerische Lebensdauerberechnung; Polyurethan-Klebstoffe; semistrukturelle Klebverbindungen; hyperelastische Klebverbindungen; Hyperelastizität; mehrachsige Klebschichtbeanspruchung; zyklische Klebschichtbeanspruchung

Android App Analysis Benchmark Case Generation - Schott, Stefan

Development Process for Smart Service Strategies: Grasping the Potentials of Digitalization for Servitization - Koldewey, Christian; Gausemeier, Jürgen; Dumitrescu, Roman; Evers, Hans-Heinrich; Frank, Maximilian; Reinhold, Jannik (Digitalization)

Digital Knowledge Base for Industrial Augmented Reality Systems Based on Semantic Technologies - Eckertz, Daniel; Möller, Marus; Anacker, Harald; Dumitrescu, Roman (Proceedings of the International Conference on Information and Computer Technologies)

MCTS-Based Synthesis Towards Efficient Approximate Accelerators - Awais, Muhammad; Platzner, Marco (Proceedings of IEEE Computer Society Annual Symposium on VLSI)
Approximate computing (AC) has acquired significant maturity in recent years as a promising approach to obtain energy and area-efficient hardware. Automated approximate accelerator synthesis involves a great deal of complexity on the size of design space which exponentially grows with the number of possible approximations. Design space exploration of approximate accelerator synthesis is usually targeted via heuristic-based search methods. The majority of existing frameworks prune a large part of the design space using a greedy-based approach to keep the problem tractable. Therefore, they result in inferior solutions since many potential solutions are neglected in the pruning process without the possibility of backtracking of removed approximate instances. In this paper, we address the aforementioned issue by adopting Monte Carlo Tree Search (MCTS), as an efficient stochastic learning-based search algorithm, in the context of automated synthesis of approximate accelerators. This enables the synthesis frameworks to deeply subsamples the design space of approximate accelerator synthesis toward most promising approximate instances based on the required performance goals, i.e., power consumption, area, or/and delay. We investigated the challenges of providing an efficient open-source framework that benefits analytical and search-based approximation techniques simultaneously to both speed up the synthesis runtime and improve the quality of obtained results. Besides, we studied the utilization of machine learning algorithms to improve the performance of several critical steps, i.e., accelerator quality testing, in the synthesis framework. The proposed framework can help the community to rapidly generate efficient approximate accelerators in a reasonable runtime.
Keywords: Approximate computing; Design space exploration; Accelerator synthesis

Funktionsoptimierte AM-Gestaltung eines E-Rotors - Magerkohl, Sebastian; Zimmer, Detmar; Tasche, Lennart; Schaper, Mirko; Urbanek, Stefan; Ponick, Bernd (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)
Die Additive Fertigung bietet ein hohes Maß an Gestaltungsfreiheit und ermöglicht die wirt-schaftliche Nutzung von konventionell schwer zu verarbeitenden Materialien. Diese Merk-male ermöglichen neuartige Lösungsansätze bei Funktionsbauteilen in fast allen Anwen-dungsbereichen. Dieses Potential kann auch im Elektromaschinenbau genutzt werden. Am Bespiel des Rotors einer permanentmagneterregten Synchronmaschine (PMSM) lassen sich die Herausforderungen und Möglichkeiten exemplarisch beschreiben.

The Meant, the Said, and the Understood: Conversational Argument Search and Cognitive Biases - Kiesel, Johannes; Spina, Damiano; Wachsmuth, Henning; Stein, Benno (Proceedings of the 2021 Conversational User Interfaces Conference)

Toward Audience-aware Argument Generation - Alshomary, Milad; Wachsmuth, Henning (Patterns)

Nonlinear metasurface combining telecom-range intersubband transitions in GaN/AlN quantum wells with resonant plasmonic antenna arrays - Mundry, Jan; Spreyer, Florian; Jmerik, Valentin; Ivanov, Sergey; Zentgraf, Thomas; Betz, Markus (Optical Materials Express)
We realize and investigate a nonlinear metasurface taking advantage of intersubband transitions in ultranarrow GaN/AlN multi-quantum well heterostructures. Owing to huge band offsets, the structures offer resonant transitions in the telecom window around 1.55 µm. These heterostructures are functionalized with an array of plasmonic antennas featuring cross-polarized resonances at these near-infrared wavelengths and their second harmonic. This kind of nonlinear metasurface allows for substantial second-harmonic generation at normal incidence which is completely absent for an antenna array without the multi-quantum well structure underneath. While the second harmonic is originally radiated only into the plane of the quantum wells, a proper geometrical arrangement of the plasmonic elements permits the redirection of the second-harmonic light to free-space radiation, which is emitted perpendicular to the surface.

Dynamische Simulation von Gefahrensituationen bei industriellen Kreislaufprozessen am Beispiel der chemischen Absorption - Bothe, Mike; Lutters, Nicole; Kenig, Eugeny

Development of Methods for Coil-Based Localization by Magnetic Fields of Miniaturized Sensor Platforms in Bioprocesses - Lange, Sven; Schröder, Dominik; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (22nd IEEE International Conference on Industrial Technology (ICIT))
In this publication important aspects for the implementation of inductive locating are explained. The miniaturized sensor platform called Sens-o-Spheres is used as an application of this locating method. The sensor platform is applied in bioreactors in order to obtain the environmental parameters, which makes a localization by magnetic fields necessary. Since the properties of magnetic fields in the localization area are very different from the wave characteristics, the principle of inductive localization is investigated in this publication and explained by using electrical equivalent circuit diagrams. Thereby, inductive localization uses the coupling or the mutual inductivities between coils, which is noticeable by an induced voltage. Therefore some properties and procedures are explained to extract the location of Sens-o-Spheres or other industrial sensor platforms from the couplings of the coils. One method calculates the location from an adapted ratio calculation and the other method uses neural networks and stochastic filters to obtain the results. In the end, these results are evaluated and compared.
Keywords: Location awareness; Coils; Couplings; Nonuniform electric fields; Magnetic separation; Neural networks; Training data

Detection of Defects on Irregular Structured Surfaces by Image Processing Methods for Feature Extraction - Sander, Tom; Lange, Sven; Hilleringmann, Ulrich; Geneis, Volker; Hedayat, Christian; Kuhn, Harald; Gockel, Franz-Barthold (22nd IEEE International Conference on Industrial Technology (ICIT))
During the industrial processing of materials for the manufacture of new products, surface defects can quickly occur. In order to achieve high quality without a long time delay, it makes sense to inspect the work pieces so that defective work pieces can be sorted out right at the beginning of the process. At the same time, the evaluation unit should come close the perception of the human eye regarding detection of defects in surfaces. Such defects often manifest themselves by a deviation of the existing structure. The only restriction should be that only matt surfaces should be considered here. Therefore in this work, different classification and image processing algorithms are applied to surface data to identify possible surface damages. For this purpose, the Gabor filter and the FST (Fused Structure and Texture) features generated with it, as well as the salience metric are used on the image processing side. On the classification side, however, deep neural networks, Convolutional Neural Networks (CNN), and autoencoders are used to make a decision. A distinction is also made between training using class labels and without. It turns out later that the salience metric are best performed by CNN. On the other hand, if there is no labeled training data available, a novelty classification can easily be achieved by using autoencoders as well as the salience metric and some filters.
Keywords: Image Processing; Defect Detection; wooden surfaces; Machine Learning; Neural Networks

Implementation and Profiling of XCS in the Context of Embedded Systems - Brede, Mathis
This bachelor thesis presents a C/C++ implementation of the XCS algorithm for an embedded system and profiling results concerning the execution time of the functions. These are then analyzed in relation to the input characteristics of the examined learning environments and compared with related work. Three main conclusions can be drawn from the measured results. First, the maximum size of the population of the classifiers influences the runtime of the genetic algorithm; second, the size of the input space has a direct effect on the execution time of the matching function; and last, a larger action space results in a longer runtime generating the prediction for the possible actions. The dependencies identified here can serve to optimize the computational efficiency and make XCS more suitable for embedded systems.

Zukunftstechnologie und moderne Antriebe kombiniert: AM in modularen Antriebssystemen - Zimmer, Detmar; Koers, Thorsten; Bührmann, Tobias (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Credal Self-Supervised Learning - Lienen, Julian; Hüllermeier, Eyke (arXiv:2106.11853)
Self-training is an effective approach to semi-supervised learning. The key idea is to let the learner itself iteratively generate "pseudo-supervision" for unlabeled instances based on its current hypothesis. In combination with consistency regularization, pseudo-labeling has shown promising performance in various domains, for example in computer vision. To account for the hypothetical nature of the pseudo-labels, these are commonly provided in the form of probability distributions. Still, one may argue that even a probability distribution represents an excessive level of informedness, as it suggests that the learner precisely knows the ground-truth conditional probabilities. In our approach, we therefore allow the learner to label instances in the form of credal sets, that is, sets of (candidate) probability distributions. Thanks to this increased expressiveness, the learner is able to represent uncertainty and a lack of knowledge in a more flexible and more faithful manner. To learn from weakly labeled data of that kind, we leverage methods that have recently been proposed in the realm of so-called superset learning. In an exhaustive empirical evaluation, we compare our methodology to state-of-the-art self-supervision approaches, showing competitive to superior performance especially in low-label scenarios incorporating a high degree of uncertainty.

A continuous strategy for collisionless gathering - Li, Shouwei; Markarian, Christine; Meyer auf der Heide, Friedhelm; Podlipyan, Pavel (Theoretical Computer Science)
Over the past decades, the Gathering problem, which asks to gather a group of robots in finite time given some restrictions, has been intensively studied. In this paper, we are given a group of n autonomous, dimensionless, deterministic, and anonymous robots, with bounded viewing range. Assuming a continuous time model, the goal is to gather these robots into one point in finite time. We introduce a simple convergence criterion that defines a new class of algorithms which perform gathering in O(nd) time, where d is the diameter of the initial robot configuration. We show that some gathering algorithms in the literature belong to this class and propose two new algorithms that belong to this class and have quadratic running time, namely, Go-To-The-Relative-Center algorithm (GTRC) and Safe-Go-To-The-Relative-Center algorithm (S-GTRC). We prove that the latter can perform gathering without collision by using a slightly more complex robot model: non oblivious, chiral, and luminous (i.e. robots have observable external memory, as in [8]). We also consider a variant of the Gathering problem, the Near-Gathering problem, in which robots must get close to each other without colliding. We show that S-GTRC solves the Near-Gathering problem in quadratic time and assumes a weaker robot model than the one assumed in the current state-of-the-art.
Keywords: Local algorithms; Distributed algorithms; Collisionless gathering; Mobile robots; Multiagent system

The impact of the Gabriel subgraph of the visibility graph on the gathering of mobile autonomous robots - Li, Shouwei; Meyer auf der Heide, Friedhelm; Podlipyan, Pavel (Theoretical Computer Science)
In this paper, we reconsider the well-known discrete, round-based Go-To-The-Center algorithm due to Ando, Suzuki, and Yamashita [2] for gathering n autonomous mobile robots with limited viewing range in the plane. Remarquably, this algorithm exploits the fact that during its execution, many collisions of robots occur. Such collisions are interpreted as a success because it is assumed that such collided robots behave the same from now on. This is acceptable under the assumption that each robot is represented by a single point. Otherwise, collisions should be avoided. In this paper, we consider a continuous Go-To-The-Center algorithm in which the robots continuously observe the positions of their neighbors and adapt their speed (assuming a speed limit) and direction. Our first results are time bounds of O(n2) for gathering in two dimensions Euclidean space, and Θ(n) for the one dimension. Our main contribution is the introduction and evaluation of a continuous algorithm which performs Go-To-The-Center considering only the neighbors of a robot with respect to the Gabriel subgraph of the visibility graph, i.e. Go-To-The-Gabriel-Center algorithm. We show that this modification still correctly executes gathering in one and two dimensions, with the same time bounds as above. Simulations exhibit a severe difference of the behavior of the Go-To-The-Center and the Go-To-The-Gabriel-Center algorithms: Whereas lots of collisions occur during a run of the Go-To-The-Center algorithm, typically only one, namely the final collision occurs during a run of the Go-To-The-Gabriel-Center algorithm. We can prove this “collisionless property” of the Go-To-The-Gabriel-Center algorithm for one dimension. In two-dimensional Euclidean space, we conjecture that the “collisionless property” holds for almost every initial configuration. We support our conjecture with measurements obtained from the simulation where robots execute both continuous Go-To-The-Center and Go-To-The-Gabriel-Center algorithms.
Keywords: Local algorithms; Distributed algorithms; Collisionless gathering; Mobile robots; Multiagent system

Quantifying the Impact of Location Data for Real Estate Appraisal – A GIS-based Deep Learning Approach - Kucklick, Jan-Peter; Müller, Jennifer; Beverungen, Daniel; Müller, Oliver (European Conference on Information Systems)

A new Device for Determination of Forming-Limit-Curves under Hot-Forming Conditions - Triebus, Marcel; Gierse, Jan; Marten, Thorsten; Tröster, Thomas (IOP Conference Series: Materials Science and Engineering)

COVID-19 reporting and willingness to pay for leisure activities - Warkulat, Sonja; Krull, Sebastian; Ortmann, Regina; Klocke, Nina; Pelster, Matthias (Covid Economics)
The containment of COVID-19 critically hinges on individuals’ behavior. We investigate how individuals react to variations in COVID-19 reporting. Using a survey, we elicit individuals' perceived infection risk given various COVID-19 metrics (e.g., confirmed cases, reproduction rate, or case-fatality ratio). We proxy individuals' risk perception with their willingness to pay for the participation in everyday life and amusements events. We find that participants react to different COVID-19 metrics with varying sensitivity. We observe a saturation of sensitivity for several measures at critical limits used in the political discussion, making our results highly relevant for policy makers in their efforts to direct individuals to adhere to hygienic etiquette and social distancing guidelines.
Keywords: COVID-19 reporting; willingness to pay; willingness to accept

Adaptation and Optimization of Planar Coils for a More Accurate and Far-Reaching Magnetic Field-Based Localization in the Near Field - Lange, Sven; Hedayat, Christian; Kuhn, Harald; Hilleringmann, Ulrich (2021 Smart Systems Integration (SSI))
In this publication, further elements of the newly developed inductive localization in the near field are presented. The advantage of inductive localization is the usage of the magnetic fields, which have a very low influence of non-metallic materials in the environment and thus follows good applications in the area of medicine and biochemistry. This allows a precise localization of sensor platforms in inhomogeneous mixtures of materials, where classical methods have major problems with inhomogeneous dielectric conductivity or density. The calculation of the localization of the searched object differs from other methods such as ultrasound or electromagnetic waves due to the source-free propagation of the magnetic field. Therefore, new mathematical evaluation methods and systematic adaptations are necessary, which are presented in this paper in circuit analysis. For this purpose, the exact circuit influences of one coil and the influence of another coil are investigated and which resonance circuit should be selected for both coils for a inductive localization with optimized signal strength.
Keywords: Electrotechnical Characteristics of Real Coils; Inductive Localization; Resonant Circuit; Mutual Inductance; Near-Field

Selective area growth of cubic gallium nitride on silicon (001) and 3C-silicon carbide (001) - Meier, F.; Protte, M.; Baron, E.; Feneberg, M.; Goldhahn, R.; Reuter, Dirk; As, D. J. (AIP Advances)

The Power and Peril of Precise vs. Round Health Message Interventions to Increase Stair-Use - Krull, Sebastian; Loschelder, David D.; Boecker, Lea (Frontiers in Psychology)

Nanoscale Surface Topography Modulates hIAPP Aggregation Pathways at Solid–Liquid Interfaces - Hanke, Marcel; Yang, Yu; Ji, Yuxin; Grundmeier, Guido; Keller, Adrian (International Journal of Molecular Sciences)
The effects that solid–liquid interfaces exert on the aggregation of proteins and peptides are of high relevance for various fields of basic and applied research, ranging from molecular biology and biomedicine to nanotechnology. While the influence of surface chemistry has received a lot of attention in this context, the role of surface topography has mostly been neglected so far. In this work, therefore, we investigate the aggregation of the type 2 diabetes-associated peptide hormone hIAPP in contact with flat and nanopatterned silicon oxide surfaces. The nanopatterned surfaces are produced by ion beam irradiation, resulting in well-defined anisotropic ripple patterns with heights and periodicities of about 1.5 and 30 nm, respectively. Using time-lapse atomic force microscopy, the morphology of the hIAPP aggregates is characterized quantitatively. Aggregation results in both amorphous aggregates and amyloid fibrils, with the presence of the nanopatterns leading to retarded fibrillization and stronger amorphous aggregation. This is attributed to structural differences in the amorphous aggregates formed at the nanopatterned surface, which result in a lower propensity for nucleating amyloid fibrillization. Our results demonstrate that nanoscale surface topography may modulate peptide and protein aggregation pathways in complex and intricate ways.

Unraveling the interaction between doxorubicin and DNA origami nanostructures for customizable chemotherapeutic drug release - Ijäs, Heini; Shen, Boxuan; Heuer-Jungemann, Amelie; Keller, Adrian; Kostiainen, Mauri A; Liedl, Tim; Ihalainen, Janne A; Linko, Veikko (Nucleic Acids Research)
Abstract Doxorubicin (DOX) is a common drug in cancer chemotherapy, and its high DNA-binding affinity can be harnessed in preparing DOX-loaded DNA nanostructures for targeted delivery and therapeutics. Although DOX has been widely studied, the existing literature of DOX-loaded DNA-carriers remains limited and incoherent. Here, based on an in-depth spectroscopic analysis, we characterize and optimize the DOX loading into different 2D and 3D scaffolded DNA origami nanostructures (DONs). In our experimental conditions, all DONs show similar DOX binding capacities (one DOX molecule per two to three base pairs), and the binding equilibrium is reached within seconds, remarkably faster than previously acknowledged. To characterize drug release profiles, DON degradation and DOX release from the complexes upon DNase I digestion was studied. For the employed DONs, the relative doses (DOX molecules released per unit time) may vary by two orders of magnitude depending on the DON superstructure. In addition, we identify DOX aggregation mechanisms and spectral changes linked to pH, magnesium, and DOX concentration. These features have been largely ignored in experimenting with DNA nanostructures, but are probably the major sources of the incoherence of the experimental results so far. Therefore, we believe this work can act as a guide to tailoring the release profiles and developing better drug delivery systems based on DNA-carriers.

Scaling Up DNA Origami Lattice Assembly. - Xin, Y; Shen, B; Kostiainen, MA; Grundmeier, Guido; Castro, M; Linko, V; Keller, Adrian (Chemistry – A European Journal)

Protein Adsorption at Nanorough Titanium Oxide Surfaces: The Importance of Surface Statistical Parameters beyond Surface Roughness. - Yang, Y; Knust, S; Schwiderek, S; Qin, Q; Yun, Q; Grundmeier, Guido; Keller, Adrian (Nanomaterials)

Biotemplated Lithography of Inorganic Nanostructures (BLIN) for Versatile Patterning of Functional Materials - Piskunen, Petteri; Shen, Boxuan; Keller, Adrian; Toppari, J. Jussi; Kostiainen, Mauri A.; Linko, Veikko (ACS Applied Nano Materials)

DNA Nanostructures in the Fight Against Infectious Diseases. - Smith, DM; Keller, Adrian (Advanced NanoBiomed Research)

Adsorption of SARS-CoV-2 Spike Protein S1 at Oxide Surfaces Studied by High-Speed Atomic Force Microscopy. - Xin, Y; Grundmeier, Guido; Keller, Adrian (Advanced NanoBiomed Research)

Effect of nanoscale surface topography on the adsorption of globular proteins - Yang, Yu; Yu, Mingrui; Böke, Frederik; Qin, Qin; Hübner, René; Knust, Steffen; Schwiderek, Sabrina; Grundmeier, Guido; Fischer, Horst; Keller, Adrian (Applied Surface Science)

Effect of PAA-induced surface etching on the adhesion properties of ZnO nanostructured films - Meinderink, Dennis; Kielar, C.; Sobol, O.; Ruhm, L.; Rieker, F.; Nolkemper, K.; Orive, A.G.; Ozcan, O.; Grundmeier, Guido (International Journal of Adhesion and Adhesives)

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg K. N.; Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)

Recent progress on metasurfaces: applications and fabrication - Yoon, Gwanho; Tanaka, Takuo; Zentgraf, Thomas; Rho, Junsuk (Journal of Physics D: Applied Physics)

Ion Beam Nanopatterning of Biomaterial Surfaces - Yang, Yu; Keller, Adrian (Applied Sciences)
Ion beam irradiation of solid surfaces may result in the self-organized formation of well-defined topographic nanopatterns. Depending on the irradiation conditions and the material properties, isotropic or anisotropic patterns of differently shaped features may be obtained. Most intriguingly, the periodicities of these patterns can be adjusted in the range between less than twenty and several hundred nanometers, which covers the dimensions of many cellular and extracellular features. However, even though ion beam nanopatterning has been studied for several decades and is nowadays widely employed in the fabrication of functional surfaces, it has found its way into the biomaterials field only recently. This review provides a brief overview of the basics of ion beam nanopatterning, emphasizes aspects of particular relevance for biomaterials applications, and summarizes a number of recent studies that investigated the effects of such nanopatterned surfaces on the adsorption of biomolecules and the response of adhering cells. Finally, promising future directions and potential translational challenges are identified.

Entwicklung einer gewichtsoptimierten Batteriegehäusestruktur für Volumenfahrzeuge - Schmolke, Tobias; Krüger, Christopher; Merdivan, David; Spohr, Sebastian; Meschut, Gerson

Experimentelle Untersuchung der Visualisierung von Geschäftsmodell-Abhängigkeiten und dessen Auswirkung auf das Verständnis der Nutzer von Geschäftsmodellen - Frieden, Paula

Nonlinear down-conversion in a single quantum dot - Jonas, B.; Heinze, D.; Schöll, E.; Kallert, P.; Langer, T.; Krehs, S.; Widhalm, A.; Jöns, K. D.; Reuter, D.; Schumacher, S.; Zrenner, Artur (arXiv:2105.12393)
Photonic quantum technologies [1] with applications in quantum communication, sensing as well as quantum simulation and computing, are on the verge of becoming commercially available. One crucial building block are tailored nanoscale integratable quantum light sources, matching the specific needs of use-cases. Several different approaches to realize solid-state quantum emitters [2] with high performance [3] have been pursued. However, the properties of the emitted single photons are always defined by the individual quantum light source and despite numerous quantum emitter tuning techniques [4-7], scalability is still a major challenge. Here we show an emitter-independent method to tailor and control the properties of the single photon emission. We demonstrate a laser-controlled down-conversion process from an excited state of a quantum three-level system [8]. Starting from a biexciton state, a tunable control laser field defines a virtual state in a stimulated process. From there, spontaneous emission to the ground state leads to optically controlled single photon emission. Based on this concept, we demonstrate energy tuning of the single photon emission with a control laser field. The nature of the involved quantum states furthermore provides a unique basis for the future control of polarization and bandwidth, as predicted by theory [9,10]. Our demonstration marks an important step towards tailored single photon emission from a photonic quantum system based on quantum optical principles.

Automating Model Transformations for Railway Systems Engineering. - Weidmann, Nils; Salunkhe, Shubhangi; Anjorin, Anthony; Yigitbas, Enes; Engels, Gregor (The Journal of Object Technology)

Enhancing Human-in-the-Loop Adaptive Systems through Digital Twins and VR Interfaces - Yigitbas, Enes; Karakaya, Kadiray; Jovanovikj, Ivan; Engels, Gregor (2021 International Symposium on Software Engineering for Adaptive and Self-Managing Systems (SEAMS))

Electrografting of 4-Nitrobenzenediazonium Salts on Al-7075 Alloy Surfaces—The Role of Intermetallic Particles - Su, Jiangling; Calderón Gómez, Juan Carlos; Grundmeier, Guido; González Orive, Alejandro (Nanomaterials)
In this work, the electrografting of Al-7075 aluminium alloy substrates with 4-nitrobenzenediazonium salt (4-NBD) films was studied on a complex aluminium alloy surface. Prior to the electrografting reaction, the substrates were submitted to different surface treatments to modify the native aluminium oxide layer and unveil intermetallic particles (IMPs). The formation of the 4-NBD films could be correlated with the passive film state and the distribution of IMPs. The corresponding electrografting reaction was performed by cyclic voltammetry which allowed the simultaneous analysis of the redox reaction by a number of complementary surface-analytical techniques. Spatially resolved thin film analysis was performed by means of SEM-EDX, AFM, PM-IRRAS, Raman spectroscopy, XPS, and SKPFM. The collected data show that the 4-NBD film is preferentially formed either on the Al oxide layer or the IMP surface depending on the applied potential range. Potentials between −0.1 and −1.0 VAg/AgCl mostly generated nitrophenylene films on the oxide covered aluminium, while grafting between −0.1 and −0.4 VAg/AgCl favours the growth of these films on IMPs.

Automated Machine Learning, Bounded Rationality, and Rational Metareasoning - Hüllermeier, Eyke; Mohr, Felix; Tornede, Alexander; Wever, Marcel Dominik

Replacing the Ex-Def Baseline in AutoML by Naive AutoML - Mohr, Felix; Wever, Marcel Dominik

Strain-Dependent Adsorption of Pseudomonas aeruginosa-Derived Adhesin-like Peptides at Abiotic Surfaces - Yang, Yu; Schwiderek, Sabrina; Grundmeier, Guido; Keller, Adrian (Micro)
Implant-associated infections are an increasingly severe burden on healthcare systems worldwide and many research activities currently focus on inhibiting microbial colonization of biomedically relevant surfaces. To obtain molecular-level understanding of the involved processes and interactions, we investigate the adsorption of synthetic adhesin-like peptide sequences derived from the type IV pili of the Pseudomonas aeruginosa strains PAK and PAO at abiotic model surfaces, i.e., Au, SiO2, and oxidized Ti. These peptides correspond to the sequences of the receptor-binding domain 128–144 of the major pilin protein, which is known to facilitate P. aeruginosa adhesion at biotic and abiotic surfaces. Using quartz crystal microbalance with dissipation monitoring (QCM-D), we find that peptide adsorption is material- as well as strain-dependent. At the Au surface, PAO(128–144) shows drastically stronger adsorption than PAK(128–144), whereas adsorption of both peptides is markedly reduced at the oxide surfaces with less drastic differences between the two sequences. These observations suggest that peptide adsorption is influenced by not only the peptide sequence, but also peptide conformation. Our results furthermore highlight the importance of molecular-level investigations to understand and ultimately control microbial colonization of surfaces.

On Strong Observational Refinement and Forward Simulation - Derrick, John; Doherty, Simon; Dongol, Brijesh; Schellhorn, Gerhard; Wehrheim, Heike (Proceedings of the 35th International Symposium on Distributed Computing (DISC))

Concurrent model synchronisation with multiple objectives - Weidmann, Nils; Engels, Gregor (Proceedings of the Genetic and Evolutionary Computation Conference)

Kraftsensitive Kalibriermethode für Industrieroboter - Schütz, Stefan; Elsner, Nikolaus; Henke, Christian; Trächtler, Ansgar (Fachtagung VDI MECHATRONIK 2021)

Echtzeitfähige Planung optimierter Trajektorien für sensorgeführte, kinematisch redundante Robotersysteme auf einer Industriesteuerung - Schütz, Stefan; Rüting, Arne Thorsten; Henke, Christian; Trächtler, Ansgar (at-Automatisierungstechnik)

Magnesium-Free Immobilization of DNA Origami Nanostructures at Mica Surfaces for Atomic Force Microscopy - Xin, Yang; Zargariantabrizi, Amir Ardalan; Grundmeier, Guido; Keller, Adrian (Molecules)
DNA origami nanostructures (DONs) are promising substrates for the single-molecule investigation of biomolecular reactions and dynamics by in situ atomic force microscopy (AFM). For this, they are typically immobilized on mica substrates by adding millimolar concentrations of Mg2+ ions to the sample solution, which enable the adsorption of the negatively charged DONs at the like-charged mica surface. These non-physiological Mg2+ concentrations, however, present a serious limitation in such experiments as they may interfere with the reactions and processes under investigation. Therefore, we here evaluate three approaches to efficiently immobilize DONs at mica surfaces under essentially Mg2+-free conditions. These approaches rely on the pre-adsorption of different multivalent cations, i.e., Ni2+, poly-l-lysine (PLL), and spermidine (Spdn). DON adsorption is studied in phosphate-buffered saline (PBS) and pure water. In general, Ni2+ shows the worst performance with heavily deformed DONs. For 2D DON triangles, adsorption at PLL- and in particular Spdn-modified mica may outperform even Mg2+-mediated adsorption in terms of surface coverage, depending on the employed solution. For 3D six-helix bundles, less pronounced differences between the individual strategies are observed. Our results provide some general guidance for the immobilization of DONs at mica surfaces under Mg2+-free conditions and may aid future in situ AFM studies.

Output tracking for a non-minimum phase robotic manipulator - Berger, Thomas; Lanza, Lukas Johannes (IFAC-PapersOnLine)
We exploit a recently developed funnel control methodology for linear non-minimum phase systems to design an output error feedback controller for a nonlinear robotic manipulator, which is not minimum phase. We illustrate the novel control design by a numerical case study where we simulate end-effector output tracking of the robotic manipulator.

Qualitative and Quantitative Analysis of Callgraph Algorithms for Python - Kummita, Sriteja; Piskachev, Goran; Spath, Johannes; Bodden, Eric (2021 International Conference on Code Quality (ICCQ))

Self-optimized, Intelligent Open-Loop-Controlled Steel Strip Straightening Machine for Advanced Formability - Bader, Fabian; Bathelt, Lukas; Djakow, Eugen; Homberg, Werner; Henke, Christian; Trächtler, Ansgar (Forming the Future)
Innovative self-correcting process control techniques which adapt to the initial geometric characteristics of the strip are a promising approach to fix the local varying distortion of coiled strips by optimizing the leveling process. This paper presents an innovative strategy to improve straightening of AHSS materials (1.4310). This implies optimized leveling, adding minimal plastic deformation, and, thus, strain hardening. Therefore, an “intelligent straightening machine” is being developed which will be presented. To operate an intelligent straightening machine a reliable online measurement of the surface defects is fundamentally essential. This paper describes an approach towards the measurement of a bent steel strip for an automatic straightening process. Therefore, various ways of measuring the bending curvature are investigated. Optical, tactile, and the electromagnetic induction testing MagnaTest are compared with each other. The bending measurement is linked to open-loop control, providing an optimal straightening result in regards of formability, leveling, and reduced strain hardening.

Qualitative and Quantitative Analysis of Callgraph Algorithms for PYTHON - Kummita, Sriteja; Piskachev, Goran; Spaeth, Johannes; Bodden, Eric (Proceedings of the 2021 International Conference on Code Quality (ICCQ))
As one of the most popular programming languages, PYTHON has become a relevant target language for static analysis tools. The primary data structure for performing an inter-procedural static analysis is call-graph (CG), which links call sites to potential call targets in a program. There exists multiple algorithms for constructing callgraphs, tailored to specific languages. However, comparatively few implementations target PYTHON. Moreover, there is still lack of empirical evidence as to how these few algorithms perform in terms of precision and recall. This paper thus presents EVAL_CG, an extensible framework for comparative analysis of Python call-graphs. We conducted two experiments which run the CG algorithms on different Python programming constructs and real-world applications. In both experiments, we evaluate three CG generation frameworks namely, Code2flow, Pyan, and Wala. We record precision, recall, and running time, and identify sources of unsoundness of each framework. Our evaluation shows that none of the current CG construction frameworks produce a sound CG. Moreover, the static CGs contain many spurious edges. Code2flow is also comparatively slow. Hence, further research is needed to support CG generation for Python programs.
Keywords: Static Analysis; Callgraph Analysis; Python; Qualitative Analysis; Quantitative Analysis; Empirical Evaluation

Anwendbarkeit von Requirement Mining in Benutzerrezensionen für die Entwicklung mechatronischer Produkte im B2C-Markt - Gräßler, Iris; Preuß, Daniel (Digital-Fachtagung VDI Mechatronik 2021; 24. - 25. Mrz. 2021)
In der Softwareentwicklung werden Requirement Mining-Ansätze eingesetzt, um in der Ermittlung von Anforderungen Informationen aus Benutzerrezensionen zu extrahieren. Auf der Online-Plattform Amazon werden verschiedene mechatronische Produkte des B2C-Markts vertrieben und deren Benutzerrezensionen gesammelt. Aufgrund der Komplexität mechatronischer Produkte werden Defizite selten nachvollziehbar im Benutzer-Feedback dokumentiert. In diesem Beitrag wird die Forschungsfrage beantwortet, ob Requirement Mining-Ansätze auch in der Produktgenerationenentwicklung mechatronischer Produkte des B2C-Markts anwendbar sind. Etablierte Requirement Mining-Ansätze werden in einer Literaturstudie identifiziert und die Anwendbarkeit initial bewertet. Der vielversprechendste Ansatz wird für eine weitergehende Analyse ausgewählt. Hierzu wird ein Fallbeispiel untersucht, indem Benutzeranforderungen eines Staubsauger- Roboters ausgewertet werden. Die Ergebnisse zeigen, dass die Informationsqualität hoch ist und Anforderungsingenieure diese Informationen zur Dokumentation der Bedürfnisse der Benutzer verwenden können.

A method for three-dimensional modelling of the shear-clinching process - Han, Daxin; Yang, Chen; Meschut, Gerson (ESAFORM 2021)
Three-dimensional modelling enables to determine the in-plane material flow in asymmetrical situation. Thus, the distortion of the sheets to be joined can be characterized more exactly. This study shows a method for building up a three-dimensional shear-clinching framework without damage criteria. In fact, the die-sided sheet in shear-clinching was designed as a pre-punched sheet and slugs. The material separation in the die-sided joining partner, which in two-dimensional simulation is often described by macro- and micromechanical fracture criteria, was realised in this study based on a defined contact condition. By means of a shear-cutting simulation, a correlation between the break angle and the separation stress was determined, which was used as a separation criterion in the shear-clinching simulation. The separation line was confirmed using post-particles. To validate this model, the results of the simulation using a quadratic single-point specimen were compared to the experiments with respect to the distortion of the joining partner. In general, the built three-dimensional framework provides for further tool developments with regard to the reduction of distortion in shear-clinching.

Development of a Leak Test Method for the Joining technology of Functionally Integrated Lightweight Battery Housings for Electric Vehicles - Schmolke, Tobias; Krüger, Christopher; Merdivan, David; Meschut, Gerson; Urban, Peter

Entwicklung einer Methode zur Bewertung einer stahlintensiven Mischbau-Klebverbindung eines Batteriegehäuses gegenüber mechanischer und medialer Belastung und Berücksichtigung der Interphasenstruktur - Schmolke, Tobias; Teutenberg, Dominik; Meschut, Gerson; Meinderink, Dennis; Koch, Leon; Ebbert, Christoph; Grundmeier, Guido

Auslegungsmethode für Klebverbindungen mit KTL-beschichteten Fügeteilen und polymeren, faserverstärkten Werkstoffen – Kleben auf KTL - Fischer, Elena; Schmolke, Tobias; Chudalla, Nick; Teutenberg, Dominik; Meschut, Gerson

The Agony of Finding the Right Pricing Policy for Cultural Institutions: Addressing Economic Viability and Cultural Participation through Innovative Pricing - Müller, Stefanie Jutta Marianne; Buchholz, Anna; Flath, Beate; Kundisch, Dennis; Momen Pour Tafreshi, Maryam

Towards Visualizing and Simulating Business Models in Dynamic Platform Ecosystems - Vorbohle, Christian; Gottschalk, Sebastian (Proceedings of the 29th European Conference on Information Systems (ECIS))
Platform-based business models underlie the success of many of today’s largest, fastest-growing, and most disruptive companies. Despite the success of prominent examples, such as Uber and Airbnb, creating a profitable platform ecosystem presents a key challenge for many companies across all industries. Although research provides knowledge about platforms’ different value drivers (e.g., network effects), companies that seek to transform their current business model into a platform-based one lack an artifact to reduce knowledge boundaries, collaborate effectively, and cope with the complexities and dynamics of platform ecosystems. We address this challenge by developing two artifacts and combining research from variability modeling, business model dependencies, and system dynamics. This paper presents a design science research approach to develop the platform ecosystem modeling language and the platform ecosystem development tool that support researcher and practitioner by visualizing and simulating platform ecosystems.
Keywords: Platform Ecosystems; Platform Ecosystem Modeling Language; Platform Ecosystem Development Tool; Business Models; Design Science

”Sorry, Too Much Information” Designing Online Review Systems that Support Information Search and Processing - Kutzner, K.; Stadtländer, M.; Seutter, Janina; Kundisch, Dennis; Knackstedt, R. (Proceedings of the 29th European Conference on Information Systems (ECIS))

Intrinsische Hybridverbunde für Leichtbautragstrukturen - Sander, Sascha; Bobbert, Mathias; Meschut, Gerson

Self-Learning Multi-Objective Service Coordination Using Deep Reinforcement Learning - Schneider, Stefan Balthasar; Khalili, Ramin; Manzoor, Adnan; Qarawlus, Haydar; Schellenberg, Rafael; Karl, Holger; Hecker, Artur (Transactions on Network and Service Management)
Modern services consist of interconnected components,e.g., microservices in a service mesh or machine learning functions in a pipeline. These services can scale and run across multiple network nodes on demand. To process incoming traffic, service components have to be instantiated and traffic assigned to these instances, taking capacities, changing demands, and Quality of Service (QoS) requirements into account. This challenge is usually solved with custom approaches designed by experts. While this typically works well for the considered scenario, the models often rely on unrealistic assumptions or on knowledge that is not available in practice (e.g., a priori knowledge). We propose DeepCoord, a novel deep reinforcement learning approach that learns how to best coordinate services and is geared towards realistic assumptions. It interacts with the network and relies on available, possibly delayed monitoring information. Rather than defining a complex model or an algorithm on how to achieve an objective, our model-free approach adapts to various objectives and traffic patterns. An agent is trained offline without expert knowledge and then applied online with minimal overhead. Compared to a state-of-the-art heuristic, DeepCoord significantly improves flow throughput (up to 76%) and overall network utility (more than 2x) on realworld network topologies and traffic traces. It also supports optimizing multiple, possibly competing objectives, learns to respect QoS requirements, generalizes to scenarios with unseen, stochastic traffic, and scales to large real-world networks. For reproducibility and reuse, our code is publicly available.
Keywords: network management; service management; coordination; reinforcement learning; self-learning; self-adaptation; multi-objective

Toward Understanding the Complexity of Business Models – A Taxonomy of Business Model Dependencies - Vorbohle, Christian; Szopinski, Daniel; Kundisch, Dennis (Proceedings of the 29th European Conference on Information Systems (ECIS))

Zum Zusammenhang von Berufsethos und der Berufswahlmotivation angehender Wirtschaftspädagog*innen - Goller, Michael; Ziegler, Simone (bwp@ Spezial)
Sowohl Berufsethos als auch Berufswahlmotivation tragen zu relevanten lern-, leistungs- und laufbahnbedingenden Prozessen eines Individuums bei und prägen dessen Lebensverlauf wesentlich. Während die Berufswahlmotivation bereits verstärkt im wirtschaftspädagogischen Kontext untersucht wurde, existieren zum Berufsethos von Wirtschaftspädagog*innen nur vereinzelt empirische Studien. So ist beispielsweise wenig darüber bekannt, wie das Berufsethos von Wirtschaftspädagog*innen in der Ausbildungsphase ausgeprägt ist. Auch die Erforschung des Zusammenhangs zwischen den Konstrukten des Berufsethos und der Berufswahlmotivation blieb bisher unbeachtet. In diesem Beitrag wird entsprechend dieses Forschungsdesiderats untersucht, wie das anfänglich ausgebildete Berufsethos von Wirtschaftspädagogikstudierenden in der universitären Ausbildung ausgeprägt ist, ob sich die Ausprägung nach dem angegebenen Berufswunsch der Studierenden unterscheidet und inwiefern das anfänglich ausgeprägte Berufsethos mit der Berufswahlmotivation von Studierenden zusammenhängt. Dafür wurden im Wintersemester 2019/20 an zwölf deutschen Universitäten insgesamt 879 Wirtschaftspädagogikstudierende schriftlich befragt. Die Ergebnisse zeigen, dass das anfängliche Berufsethos der Befragten bereits in der universitären Ausbildungsphase relativ stark ausgeprägt ist. Weiterhin ist zu erkennen, dass das Berufsethos bei angehenden Wirtschaftspädagog*innen, die den Berufswunsch Lehrkraft haben, ausgeprägter ist als bei Wirtschaftspädagogikstudierenden, die eine Tätigkeit außerhalb des Schuldienstes anstreben bzw. noch unentschlossen sind. Letztlich kann aufgezeigt werden, dass grundsätzlich positive Zusammenhänge zwischen dem anfänglich ausgeprägten Berufsethos und der Berufswahlmotivation von angehenden Wirtschaftspädagog*innen bestehen.
Keywords: Berufsethos; Berufswahlmotivation; Wirtschaftspädagogik; Studierende

Spectral Properties of Effective Dynamics from Conditional Expectations - Nüske, Feliks; Koltai, Péter; Boninsegna, Lorenzo; Clementi, Cecilia (Entropy)
The reduction of high-dimensional systems to effective models on a smaller set of variables is an essential task in many areas of science. For stochastic dynamics governed by diffusion processes, a general procedure to find effective equations is the conditioning approach. In this paper, we are interested in the spectrum of the generator of the resulting effective dynamics, and how it compares to the spectrum of the full generator. We prove a new relative error bound in terms of the eigenfunction approximation error for reversible systems. We also present numerical examples indicating that, if Kramers–Moyal (KM) type approximations are used to compute the spectrum of the reduced generator, it seems largely insensitive to the time window used for the KM estimators. We analyze the implications of these observations for systems driven by underdamped Langevin dynamics, and show how meaningful effective dynamics can be defined in this setting.

Mechanical joining of glass fibre reinforced polymer (GFRP) through an innovative solid self-piercing rivet - Han, Daxin; Yang, Keke; Meschut, Gerson (Journal of Materials Processing Technology)

Gattung und Geschlecht: Konventionen und Transformationen eines Paradigmas

The Black British Bildungsroman: Gender-specific Plot Models? - Tönnies, Merle (Gattung und Geschlecht: Konventionen und Transformationen eines Paradigmas)

Bilingualer Unterricht. Aktuelle Herausforderungen und neue Chancen: Zur Einführung in den Themenschwerpunkt [koordiniert von B. Diehr & D. Rumlich] - Diehr, Bärbel; Rumlich, Dominik (Fremdsprachen Lehren und Lernen)